2011
DOI: 10.1242/dev.061499
|View full text |Cite
|
Sign up to set email alerts
|

The pipsqueak-domain proteins Distal antenna and Distal antenna-related restrict Hunchback neuroblast expression and early-born neuronal identity

Abstract: SUMMARYA fundamental question in brain development is how precursor cells generate a diverse group of neural progeny in an ordered manner. Drosophila neuroblasts sequentially express the transcription factors Hunchback (Hb), Krüppel (Kr), Pdm1/Pdm2 (Pdm) and Castor (Cas). Hb is necessary and sufficient to specify early-born temporal identity and, thus, Hb downregulation is essential for specification of later-born progeny. Here, we show that distal antenna (dan) and distal antenna-related (danr), encoding pips… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 30 publications
1
56
0
Order By: Relevance
“…Seven up is expressed in two pulses in the NB5-6T lineage Previous studies revealed that Svp is expressed in two pulses during VNC development (Kanai et al, 2005;Kohwi et al, 2011). We also noted a distinct biphasic appearance of Svp expression in the VNC (not shown).…”
Section: Research Articlesupporting
confidence: 73%
See 2 more Smart Citations
“…Seven up is expressed in two pulses in the NB5-6T lineage Previous studies revealed that Svp is expressed in two pulses during VNC development (Kanai et al, 2005;Kohwi et al, 2011). We also noted a distinct biphasic appearance of Svp expression in the VNC (not shown).…”
Section: Research Articlesupporting
confidence: 73%
“…Recently, studies have identified additional factors involved in the downregulation of Hb: the pipsqueak-domain proteins Distal antenna and Distal antenna-related (herein referred to collectively as 'Dan') (Kohwi et al, 2011). Dan is expressed somewhat earlier than Svp, and is also maintained in a longer pulse.…”
Section: The Early Role Of Seven Up: a Temporal 'Switching Factor'mentioning
confidence: 99%
See 1 more Smart Citation
“…Dany's closest relatives Dan and Danr, which act partially redundantly in somatic tissues (Curtiss et al, 2007;Emerald et al, 2003;Kohwi et al, 2011Kohwi et al, , 2013, are crucial for the control of intranuclear position and silencing of the hunchback (hb) genomic locus in neuroblasts during embryogenesis (Kohwi et al, 2013). hb relocalization to the nuclear lamina, which is correlated with hb silencing and termination of Hb response competence, depends on timely Dan downregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Also, gain-offunction studies revealed that temporal TFs activate the next one in the queue and repress the next one(s) downstream, and in general terms, earlier expressed TFs in the cascade are dominant over the late ones [29,67,68]. On top of that, shifting from one temporal factor to another may also be regulated by additional factors, so-called switching TFs: Distal antenna (Dan) and Seven up (Svp) are both involved in controlling the transition from Hb to Kr within the cascade [29,69,70]. Albeit the temporal selectors play a critical role in the generation of cell type diversity, the many types of cells identified within the CNS cannot be explained exclusively by this cascade.…”
Section: Temporal Selectors Drive Cell Diversity In Developing Embryomentioning
confidence: 99%